Body wall structure in the starfish Asterias rubens. Issue 3 (16th July 2017) - Blowes, Liisa M.; Egertová, Michaela; Liu, Yankai; Davis, Graham R.; Terrill, Nick J.; Gupta, Himadri S.; Elphick, Maurice R.
Abstract: The body wall of starfish is composed of magnesium calcite ossicles connected by collagenous tissue and muscles and it exhibits remarkable variability in stiffness, which is attributed to the mechanical mutability of the collagenous component. Using the common European starfish Asterias rubens as an experimental animal, here we have employed a variety of techniques to gain new insights into the structure of the starfish body wall. The structure and organisation of muscular and collagenous components of the body wall were analysed using trichrome staining. The muscle system comprises interossicular muscles as well as muscle strands that connect ossicles with the circular muscle layer of the coelomic lining. The collagenous tissue surrounding the ossicle network contains collagen fibres that form loop‐shaped straps that wrap around calcite struts near to the surface of ossicles. The 3D architecture of the calcareous endoskeleton was visualised for the first time using X‐ray microtomography, revealing the shapes and interactions of different ossicle types. Furthermore, analysis of the anatomical organisation of the ossicles indicates how changes in body shape may be achieved by local contraction/relaxation of interossicular muscles. Scanning synchrotron small‐angle X‐ray diffraction (SAXD) scans of the starfish aboral body wall and ambulacrum were used to study the collagenous tissue component at the fibrillar level. Collagen fibrils in aboral body wall were found to exhibit variable degrees of alignment, with high levels of alignment probably corresponding to regions where collagenous tissue is under tension. Collagen fibrils in the ambulacrum had a uniformly low degree of orientation, attributed to macrocrimp of the fibrils and the presence of slanted as well as horizontal fibrils connecting antimeric ambulacral ossicles. Body wall collagen fibril D‐period lengths were similar to previously reported mammalian D‐periods, but were significantly different between the aboral and ambulacral samples. The overlap/D‐period length ratio within fibrils was higher than reported for mammalian tissues. Collectively, the data reported here provide new insights into the anatomy of the body wall in A. rubens and a foundation for further studies investigating the structural basis of the mechanical properties of echinoderm body wall tissue composites.